La historia de Aguascalientes contada por Beatriz Rojas - Gómez Serrano, Jesús (Caleidoscopio - Revista Semestral de Ciencias Sociales y Humanidades, 1999)
This article propases an analysis of the historiographic production referred to Aguascalientes during the XX century. The material is approached in a thematic way: armed revolution, destruction of haciendas and agricultural development, the history of education, the catholic church, its política! and social modernization, industrial and urban development, social movements and political development. Lt intends an evaluation of the advances that are reported in each thematic field and an analysis of the main works. At the end, sorne reflections are made on the importance of the research published and the fields were new contributions are felt necessary.